Force to Divide: Structural and Mechanical Requirements for Actomyosin Ring Contraction - Mendes Pinto, Inês (The Biophysical Society, 2013)
One of the unresolved questions in the field of cell division is how the actomyosin cytoskeleton remains structurally organized while generating the contractile force to divide one cell into two. In analogy to the actomyosin-based force production mechanism in striated muscle, it was originally proposed that contractile stress in the actomyosin ring is generated via a sliding filament mechanism within an organized sarcomere-like array. However, over the last 30 years, ultrastructural and functional studies have noted important distinctions between cytokinetic structures in dividing cells and muscle sarcomeres. Myosin-II motor activity is not always required, and there is evidence that actin depolymerization contributes to contraction. In this Review, the architecture and contractile dynamics of the actomyosin ring at the cell division plane will be discussed. We will report the interdisciplinary advances in the field as well as their integration into a mechanistic understanding of contraction in cell division and in other biological processes that rely on an actomyosin-based force-generating system.